NOVEL ISOLATED MULTI-PULSE RECTIFIERS WITH LOW CURRENT DISTORTION USING THREE-PHASE HALF-CONTROLLED BOOST CONVERTERS - Pelicer Junior, Joao Carlos [UNESP] (2015)
Since the AC-DC conversion is widely spread in power sources, this work proposes a novel strategy of multi-pulse topologies, associated to the half-controlled boost-based rectifier, which has the follows main advantages: low Total Harmonic Distortion of the line current (THDi), below 2%; Power Factor (PF) close to unit; simple gate drive circuit, since all active switches are connected to the same reference; robustness given that the DCM operation results the peaks of the current naturally follow the voltage waveform. The control circuit becomes very simplified because all the switches are synchronized and only one basic voltage loop should be used to regulate the DC output, without current sensors. In addition, the commutation process occurs after the current in the diode becomes zero (DCM), without losses and current stresses due to the diode reverse recovery. The simulation analysis shows a significant improvement of PF once the THDi is lower than 2% while the conventional 12-pulse topologies have about 14%. Each conventional three-phase bridge rectifier is replaced by a three-phase half-controlled boost-based topology, also called of bridgeless rectifiers. A 2.5 kW prototype is being built and its feature is a strong candidate for More Electric Aircraft (MEA) and Adjustable Speed Drive (ASD) applications.